Pemanfaataan Fear of Missing Out (FOMO) sebagai Strategi Pemasaran UMKM Kuliner di Kota Kupang - Septia Sakalini Dioh; Jappy P. Fanggidae; Taqwa Sultan (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2026)
Rapid advances in digital technology require Micro, Small, and Medium Enterprises (MSMEs) to be adaptable in their marketing strategies. Generation Z, as a group with a high internet penetration rate (around 70%), has given rise to the Fear of Missing Out (FOMO) phenomenon. This study aims to examine the implementation of the FOMO phenomenon as a marketing strategy among MSMEs and to analyze its effectiveness in enhancing product appeal and influencing purchasing decisions. The method used is a qualitative approach with case studies of SME operators who utilize social media as a promotional tool. The results show that the application of FOMO strategies through viral content, time-limited promotions, and the utilization of social media trends can increase the visibility of SME products and encourage consumer engagement. As a community development, FOMO has proven effective in driving of MSMEs in the digital market and improving people's purchasing decisions.